Relações entre o trabalho e a saúde das professoras de escolas públicas do município de João Pessoa- PB - Santos, Francecirly Alexandre dos (2011)
This study analyzes the relationship between work and health of teachers of the first grades of elementary in public schools in the city of João Pessoa-PB. Therefore, its takes as major theoretical references health conception proposed by Canguilhem, The Ergonomics of Activity, the psychodynamics of work and the literature on relations social gender and sexual division of labor. From the point of methodological view, it was used the three distinct and complementary steps: i) collection of books and journals which address the topic in question, ii) survey, in the County Medical Board, the profile of diseases that attack the teachers in 2009 and iii) meetings on the job with teachers from schools participating in the research. The results of epidemiological survey showed that in 2009, 398 teachers have requested medical leave, and 359 were female and 39 male, a total of 676 applications absences from work. The most frequent diagnoses were diseases of musculoskeletal system and connective tissue (21.8%), mental disorders and behavioral (14.2%). After the survey data on the educational context of the city, it was also performed observations of the activity work and meetings on the job through the establishment of Expanded Communities of Research (ECR), which had 25 (twenty five) teachers from 03 (three) public schools, 24 (twenty four) teachers were female and 01 (a) male teacher. From the observations of work activity and meetings of ECRs, we realized that the teachers in the course of drawing up regulations activity before the prescribed task and so help to preserve its health. We also perceived that their experiences of suffering and the processes of illnesses (which are underreported) are linked to forms of organization and working conditions, more specifically, to low salaries, the overhead labor and social devaluation of their contribution as a teacher. However, we found that the pleasure extracted from the recognition of students and their coworkers contributes to the health of teachers, avoiding increase in diseases, and give meaning to their work.